TATA KELOLA PERIZINAN PERKEBUNAN KELAPA SAWIT YANG TELAH TERBANGUN PADA KAWASAN HUTAN - Syahrial, Aditya Bhatara; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This paper will examine the licencing process for oil palm plantations that have been constructed within forest areas as outlined in the spatial planning regulations. This process is governed by the mechanisms specified in sections 110A and 110B of Law No. 6 of 2023, which pertain to the enactment of Perppu no. 2 of 2022 regarding job copyright into law. The question of granting licences for oil palm plants in forest regions is a contentious and intricate matter within the realms of agriculture and environmental preservation. This text centres on the procedure necessary to acquire authorization from the appropriate governing body for pre-existing oil palm farms situated within forested regions. In addition, this composition will also examine the factors that impact the establishment of existing oil palm plantations. Is situated within a wooded region, where this circumstance can also incite social discord between commercial entities and the local populace. Hence, this article will also address the necessary protocols that business entities must adhere to, in accordance with the latest legislation, to meet the growing market demand while also complying with regulations pertaining to the sustainability of oil palm plantations in forested regions .The research employs a normative methodology, utilising secondary data and employing descriptive analysis. The research findings will outline the necessary steps that business actors must take to acquire permissions for the ongoing operation of oil palm plantations established in forest areas lacking proper authorization within the designated region. A dense collection of trees and vegetation.Keywords : Palm Oil Plantations, Licensing, Forest Areas